Design Process for Dual-Purpose Nuclear Spent Fuel Casks. (September 2017) - Palacio, Alejandro
Abstract: Nuclear spent fuel management has become a key activity within national nuclear strategies. Spent fuel casks shall be customized, in order to release space in the pools of the nuclear power plants to continue operating. The final goal is to complete the decommissioning activities in some nuclear facilities or to load spent fuel with new enhanced irradiation parameters. Cask designers develop complex technical processes that require very skilled staff to understand and compile the requirements of the cask users. It's necessary to adapt and validate the cask design concepts to comply with the applicable regulation. Finally, it is required to provide the detailed technical documentation as well as appropriate justifications to the nuclear regulators, for the safe management of the nuclear spent fuel.